Izbrannye proizvedenija v šesti tomach. Pod red. V.V. Adoratskogo, A.I. Krinickogo [i] M.N. Pokrovskogo. Tt. 2-6 (Gosizdat i t.d., 1930)
Institut lenina pri CK VKP(B). 2. 1905-1914. 1930. VII, 760 str.